Long-Term Effect of Maternal Antioxidant Supplementation on the Lipid Profile of the Progeny According to the Sow's Parity Number - Gerardo Gómez; Hernan D. Laviano; Juan García-Casco; Maria Muñoz; Fernando Gómez; Fernando Sánchez-Esquiliche; Antonio González-Bulnes; Clemente López-Bote; Cristina Óvilo; Ana I. Rey (MDPI AG, 2024)
Pig feeding prior to the extensive fattening phase might affect the final lipid profile and product quality. This study evaluates how maternal supplementation with vitamin E (VITE) (100 mg/kg), hydroxytyrosol (HXT) (1.5 mg/kg), or combined administration (VE + HXT) affects the piglet's plasma and tissues' fatty acid profiles and lipid stability according to the sow's parity number (PN), as well as the possible changes to the lipid profile after extensive feeding. The sows' PN affected the total fatty acid profile of plasma, muscle, and liver of piglets, with lower Δ-9 and Δ-6 desaturase indices but higher Δ-5 in those from primiparous (P) than multiparous (M) sows. Dietary VITE was more effective at decreasing C16:0 and saturated fatty acids in the muscle of piglets born from M than P sows, and modified the liver phospholipids in a different way. Sows' supplementation with HXT increased C18:2n-6 in triglycerides and polyunsaturated fatty acids (PUFA) in muscle phospholipids. In the liver, HXT supplementation also increased free-PUFA and free-n-3 fatty acids. However, lipid oxidation of piglets' tissues was not affected by the antioxidant supplementation, and it was higher in the livers of piglets born from M sows. The fatty acid profile in the muscle of pigs after extensive feeding was not affected by the PN, but it was by the sows' antioxidant supplementation, with positive effects on quality by both compounds.